Gut microbiome-modulated dietary strategies in EAE and multiple sclerosis - Hoffman, Kristina; Doyle, William J.; Schumacher, Sean M.; Ochoa-Repáraz, Javier (Frontiers in Nutrition, 2023)
Over the last few decades, the incidence of multiple sclerosis has increased as society’s dietary habits have switched from a whole foods approach to a high fat, high salt, low dietary fiber, and processed food diet, termed the “Western diet.” Environmental factors, such as diet, could play a role in the pathogenesis of multiple sclerosis due to gut microbiota alterations, gut barrier leakage, and subsequent intestinal inflammation that could lead to exacerbated neuroinflammation. This mini-review explores the gut microbiome alterations of various dietary strategies that improve upon the “Western diet” as promising alternatives and targets to current multiple sclerosis treatments. We also provide evidence that gut microbiome modulation through diet can improve or exacerbate clinical symptoms of multiple sclerosis, highlighting the importance of including gut microbiome analyses in future studies of diet and disease.